Dynamic Uses of Spectrographic Analysis in Choral Rehearsals and the Voice Studio - Mark McQuade (Journal of the Association for Technology in Music Instruction, 2020)
Spectrographic analysis is a powerful tool that allows students to see a visual representation of the acoustic properties of their instruments. For today’s technologically savvy students it brings an exciting new element to music making that will allow them to grow musically, artistically, and technically even faster. With a computer, microphone, and screen (or even just a smart phone) teachers can open their students’ eyes to see what their ears have always been hearing. By turning an aural/oral art into a visual experience, students will gain a deeper understanding of their instruments and how they can use those instruments efficiently and expressively. The application of spectrographic analysis applies to both choral ensembles and vocal soloists, and while this article will focus on its use with the singing voice, spectrographic analysis also has benefits for instrumentalists as well. To understand the practical applications, we will examine a variety of vocal and musical skills that can be explored through this technology.
Keywords: Acoustics; Choir; Choral; Singing; Spectrograph; Vocal; Voice